All‐Printed, Foldable Organic Thin‐Film Transistors on Glassine Paper. (6th October 2015) - Hyun, Woo Jin; Secor, Ethan B.; Rojas, Geoffrey A.; Hersam, Mark C.; Francis, Lorraine F.; Frisbie, C. Daniel
Abstract : All‐printed, foldable organic thin‐film transistors are demonstrated on glassine paper with a combination of advanced materials and processing techniques. Glassine paper provides a suitable surface for high‐performance printing methods, while graphene electrodes and an ion–gel gate dielectric enable robust stability over 100 folding cycles. Altogether, this study features a practical platform for low‐cost, large‐area, and foldable electronics.